Pemberian Hibah Berdasarkan Peraturan Gubernur Bali Nomor 2 Tahun 2017 Tentang Pedoman Pemberian Hibah Dan Bantuan Sosial - Damayanti, Ira (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018), 2018)
This study discussed about provision of grants is based on governor regulation of Bali number 2 of 2017 on Guidelines for Grant and Social Assistance, focusing on the implementation arrangement based on related Governor regulation and its relations with Article Number 298 (5) on Law Number 23         of 2014, which has caused different interpretation about the grant provision arrangement implemented by Bali Provincial Government. The study is done by using normative legal research, along with several approaches, such as legislation approach, legal concept approach, as well as case-based approach utilizing primary an d secondary legal sources with combination of snowball technique and card system to obtain all laws and regulations related to the issue studied. The objective of this studyis to formulate solutiontothe conflicting norms in the existing legislation in order to provide legal certainty for the community. The study shows that grant provision arrangement implemented by Bali Provincial Government is based on Bali Governor Regulation, Provision which was formulated based on Regulation of the Minister of Home Affairs Number 14 Year 2016 on the Second Amendment to the Regulation of the Minister of Home Affairs Number 32 Year 2011. It is found that the source of the conflicting norm sinimplementing grant provision at Bali Province comes fom the inconsistency between those regulations because the afore mentioned Governor Regulation has arranged for a logical flow of grant provision to community organizations not listed in the ministerial decree in order to support cultural sustain ability and development in Bali.